NYALA API ASMARA HADI - Sutiana, Agus (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
Nyala Api Asmara Hadi is a documentary film that raised about the life history and gait of Asmara Hadi as a multitalented person, where he was active in the struggle movement, became a writer and also a journalist. Asmara Hadi is also known as the son of Bung Karno's ideology, he is also known as someone who proposes the name Panca Sila. Asmara Hadi's life journey was lifted with a portrait of documentary style and documentary nostalgia with the main source, his own child and some of his comrades. It is intended that the disclosure of Asmara Hadi is based on an objective and correct view.